2015
DOI: 10.1158/1535-7163.mct-14-0580
|View full text |Cite
|
Sign up to set email alerts
|

Tumor-Associated Hyaluronan Limits Efficacy of Monoclonal Antibody Therapy

Abstract: Despite tremendous progress in cancer immunotherapy for solid tumors, clinical success of monoclonal antibody (mAb) therapy is often limited by poorly understood mechanisms associated with the tumor microenvironment (TME). Accumulation of hyaluronan (HA), a major component of the TME, occurs in many solid tumor types, and is associated with poor prognosis and treatment resistance in multiple malignancies. In this study, we describe that a physical barrier associated with high levels of HA (HA high ) in the TME… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
101
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 116 publications
(106 citation statements)
references
References 48 publications
5
101
0
Order By: Relevance
“…31,32 In vitro and in vivo studies have shown that depletion of HA as a result of treatment with PEGPH20 leads to increased natural killer (NK) cell access to HAHigh tumor cells and enhanced trastuzumab or cetuximab-antibodydependent cell-mediated cytotoxicity. 17 This further supports the belief that surrounding PDA tumors, the HA matrix forms a barrier that inhibits monoclonal antibody and NK cell access; this barrier can be overcome using PEGPH20. In tumor cell membranes, CD44 receptors and receptors for hyaluronan mediated motility (RHAMM) bind and anchor the HA matrix, and this association is believed to enhance receptor tyrosine kinase activity that drives tumor progression and increases treatment resistance.…”
Section: Mechanism Of Actionsupporting
confidence: 62%
See 2 more Smart Citations
“…31,32 In vitro and in vivo studies have shown that depletion of HA as a result of treatment with PEGPH20 leads to increased natural killer (NK) cell access to HAHigh tumor cells and enhanced trastuzumab or cetuximab-antibodydependent cell-mediated cytotoxicity. 17 This further supports the belief that surrounding PDA tumors, the HA matrix forms a barrier that inhibits monoclonal antibody and NK cell access; this barrier can be overcome using PEGPH20. In tumor cell membranes, CD44 receptors and receptors for hyaluronan mediated motility (RHAMM) bind and anchor the HA matrix, and this association is believed to enhance receptor tyrosine kinase activity that drives tumor progression and increases treatment resistance.…”
Section: Mechanism Of Actionsupporting
confidence: 62%
“…13,14 Accumulation of HA in tumors may also act as a barrier to immune cells, including T lymphocytes and macrophages, creating an immune suppressed microenvironment. [15][16][17] Increased HA also prevents chemotherapeutic agents and monoclonal antibodies from reaching their sites of action. 8,9 HA accumulation in the TME is associated with accelerated tumor growth and is an independent, negative predictor of survival.…”
Section: The Tumor Microenvironmentmentioning
confidence: 99%
See 1 more Smart Citation
“…Cells which have undergone EMT often present with an altered glycocalyx, the saccharide-protein network on the cell surface (Roy et al, 2011;Porsch et al, 2013;Moustakas and Heldin, 2014). A strong glycocalyx elicits pro-tumorigenic effects by enhancing focal adhesion formation and downstream signaling (Paszek et al, 2014), and has also been implicated in resistance to small-molecule and antibody therapies because it provides a physical shield to the cell membrane and its associated receptors (Yang et al, 2013;Thompson et al, 2010;Singha et al, 2015). Indeed, in GBMs, we find that glycocalyx bulk augments mechanical signaling (unpublished data).…”
Section: Effects Of Mechanical Changes On Glioma Progressionmentioning
confidence: 61%
“…Regardless of the advances in pancreatic tumor biology knowledgment, mechanisms associated with the tumor microenvironment remain poorly understood, highlighting that the distinct composition of pancreatic tumor microenvironment could be a great barrier for immunotherapy success [92] . As a consequence of newly emerging information about tumor microenvironment, there was a shift in the cancer development concept from a tumor cell-centered view to a complex tumor ecosystem, which led to the acceptance that cancer cells interact with the extracellular matrix (ECM) and stromal cells [93,94] .…”
Section: Gm-csf Vaccinesmentioning
confidence: 99%